(untitled) (Revista Direitos Humanos e Democracia, 2025)
This study investigates the impact of the stigma associated with being a refugee on the (in)effectiveness of personality rights in the post-truth era. The stigma intensifies the vulnerability of refugees, perpetuating cycles of exclusion and dehumanization. The research also explores how the post-truth era contributes to the perpetuation of stigmatizing narratives, which oscillate between portraying refugees as "pitiful" or "parasites." The theoretical approach, combining quantitative and qualitative methods, examines how these perceptions influence anti-immigration policies and social reception in host countries. The analysis reveals that the crisis faced is both migratory and human rights-related, where the dignity of refugees is constantly threatened by misinformation and the manipulation of narratives. The study concludes that stigma and post-truth, working together, become powerful tools in the erosion of refugee rights, contributing to their social marginalization.